Malondialdehyde Levels in Preeclampsia before and after Delivery: Kadar Malondialdehid pada Penderita Preeklamsia Berat sebelum dan sesudah Persalinan - Harold Rumopa; Freddy W. Wagey; Eddy Suparman (Indonesian Journal of Obstetrics and Gynecology, 2018)
Objective: Determine differences plasma levels MDA in preeclampsiabefore and 2 hours after delivery. Methods: This was an analytic cross-sectional study. Subjectconsists of 23 pregnancies with preeclampsia, where 23 bloodsamples taken before delivery and 23 were taken 2 hours afterdelivery. This study was conducted from August 2016 untilDecember 2016 at Department of Obstetrics and GynecologyFaculty of Medicine Universitas Sam Ratulangi / Prof. Dr. R. D.Kandou Hospital Manado and satellite hospital. Samples weretaken from plasma and analysed using HPLC method at Prodiaclinical laboratory. Results: In patients with severe preeclampsia before deliverywe found average value (1.4796 ï‚± 0.40819 nmol/ml), minimumvalue (1.03 nmol/ml) and maximal value (2.77 nmol/ml)and 2 hours after delivery with average value (1.2470 ï‚±0.34324 nmol/ml), minimum value (0.91 nmol/ml), and maximumvalue (2.47 nmol/ml). by using Wilcoxon test, we foundthere were significant differences in plasma levels of MDA (p =0.000). Conclusion: This significant difference suggests that decreasedplasma levels of MDA 2 hours after delivery and gives the sense thatthere is a relationship between oxidative stress of cells with severepreeclampsia before and shortly after delivery, that MDA is an indicatorof oxidative stress. Keywords: malondialdehyde, oxidative stress, peroxidation lipid,preeclampsia